PUTILIZATION OF PETROCK OIL AS ALTERNATIVE FUEL MACHINES DIESEL - - Suhartanta; Zaenal Arifin (Jurnal Penelitian Saintek, 2008)
This study aims to determine the characteristics of jatropha oil biodiesel, both in terms of physics and chemistry. Biodiesel is attempted to be used as a diesel fuel substitute for diesel motors. Further analyzed differences in the performance of diesel motors when using jatropha oil biodiesel fuel and when using diesel.In its implementation, this research begins by examining jatropha oil biodiesel characteristics physically and chemically. Once tested its characteristics, the fuel is used directly on diesel engines to measure opacity, torque, power, and the amount of fuel consumption and then compared with the use of diesel fuel. The comparison analysis of jatropha oil and diesel biodiesel characteristics was all submitted to UGM Chemical Engineering Laboratory. Furthermore, for the measurement of exhaust emissions, torque, power, and fuel consumption is submitted to the Energy Conversion Laboratory of Mechanical and Industrial Engineering Department of FT UGM. Based on the analysis of fuel characteristics, it is found that biodiesel developed as diesel engine fuel derived from jatropa oil (Jatropa Curcas L.) has the same characteristics even on some items that is on the analysis of heating value has better characteristics compared with diesel. The amount of exhaust emissions in the form of the concentration of smoke (opacity) has the greatest decrease, ie the average decrease obtained by 82%, with the best mixture at fraction of 20% .The magnitude of torque resulting from jatropha oil biodiesel testing after compared with diesel at various fractions of the mixture obtained results that the resulting torque increased by an average of 19%. The highest torque was obtained in 20% biodiesel mixture. Furthermore, the amount of power generated from the biodiesel usage of the engine produces a rise in power in the shaft at various rpm variations, and the fraction of the biodiesel mixture has an average power increase of 19%, with the highest power being obtained in the 20% mixture. Fuel consumption for Jatropha curcas biodiesel experienced an average decrease of 24.2% with the best fraction obtained in the 20% mixed fraction.